Variable pH habitats could help prepare stone crabs for coastal acidification - Philip M. Gravinese; Hannah E. Craft; Alex Douwes; Gretchen S. Faraci; Morgan L. Jarrett; Shelby A. Perry; Chloe E. Potts; Emma C. Rosser; Abigail L. Smith; Alexis R. Trevillian; Christopher Moore; Kimberly K. Yates (Marine Biology, 2026)

Relationships Between Soil and Vegetation Properties and Soil Carbon Stocks Differ Between Grasslands with Different Water Table Management - Emma M. N. Polman; Kenneth F. Rijsdijk; Perry Cornelissen; Rutger L. van Hall; Franciska T. de Vries (Ecosystems, 2026)
Water table management such as temporal flooding is an important strategy for influencing vegetation development and creating suitable habitat for wildlife in managed wetland systems. Water table fluctuations can also affect soil carbon and nutrient cycling through changes in abiotic soil properties, plant traits and soil microbial communities, but research on the effect of temporal flooding on these relations is limited. Here we tested the hypothesis that winter inundation leads to a plant community with more fast-growth-related plant traits, a bacterial-dominated soil microbial community, and lower soil organic carbon stocks compared to a year-round dry grassland. We compared soil and vegetation of winter-inundated and non-inundated grassland in a Dutch-managed wetland area. In contrast to our hypothesis, we found that winter inundation results in plant communities with more slow-growth-related traits and microbial communities more dominated by fungi, compared to non-inundated grassland. We found no difference between shallow soil organic carbon stocks, carbon-to-nitrogen ratios or nitrogen-to-phosphorous ratios. Winter inundation did, however, change the relationship between soil and vegetation properties and soil carbon stocks, as well as soil nutrient ratios. While soil carbon stocks in non-inundated grassland were explained by abiotic soil and vegetation properties, soil carbon stocks were only explained by microbial properties in winter-inundated grasslands. These findings show that winter inundation can be used for vegetation and wildlife management with limited effects on soil carbon stocks.

National-scale river water quality in the Philippines: establishing baselines in a mineralised megadiverse nation - Emma Biles; Richard David Williams; Decibel Faustino-Eslava; Loucel Cui; Francis Ian Gonzalvo; Kim Bryan Cabrera; Manilyn Casa; Craig MacDonell; Maria Regina V. Regalado; Laura Quick; Justine Perry Domingo; Trevor Hoey; et al. (Science of The Total Environment, 2026)

Surface-modified cellulose nanofibrils (CNFs) with enhanced functionality for potential food applications - SuriyaPrakaash LakshmiBalasubramaniam; S. Shams Es-haghi; Mehdi Tajvidi; Emma Perry; Denise Skonberg (Food Bioscience, 2025)

The Cost of Antivenom: A Cost Minimization Study using the North American Snakebite Registry - Benjamin Herzel; Neev Batavia; Paul Gavaza; Tammy Phan; Emmelyn Samones; Anne-Michelle Ruha; Jakub Furmaga; Christopher Hoyte; Brian J. Wolk; Peter Akpunonu; Adam Algren; Alexandra Amaducci; et al. (Journal of Medical Toxicology, 2025)
Envenomation is a global health issue, with over 9,000 encounters managed in the United States yearly. The introduction of immunoglobulin fragment antivenom has reduced the risk of hypersensitivity. This study compares treatment costs of crotaline envenomation using the Fab and F(ab’) 2 antivenoms as reported to the North American Snakebite Registry (NASBR), a nationwide surveillance tool. Methods This was a retrospective analysis of NASBR data between 2018 and 2020. The following data points were assessed: patient demographics (age, gender, race), snake species, type of antivenom used, and treatment costs. Unit costs were estimated based on United States Centers for Medicare and Medicaid Services data. Average (mean) per patient costs from the payer perspective were calculated by multiplying resources by the unit costs. Sensitivity analyses were performed regarding cost variance and snake species. All costs reported in this study are in U.S. dollars. Results The average total cost of treatment was $31,343 per person, with medications contributing 72% of the total. Average total cost among patients who received Fab treatments was $33,347 per person compared to $19,747 among patients who received F(ab’) 2 . Antivenom costs accounted for 75% of the total cost in the Fab group and 42% in the F(ab’) 2 group. F(ab’) 2 required more vials than Fab (median 18 versus 10). Non-antivenom costs such as hospitalizations were higher in the F(ab’) 2 group. Using average sale prices increased average total cost to $52,572; Fab remained more expensive. Conclusion Antivenom is the primary cost driver in snakebite treatment in North America. Treatment with F(ab’) 2 resulted in lower overall costs, driven by lower cost of antivenom. F(ab’) 2 did not significantly lower overall resource use except for blood product administration.

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

Sustainable mining in tropical, biodiverse landscapes: Environmental challenges and opportunities in the archipelagic Philippines - Justine Perry T. Domingo; Gawen R.T. Jenkin; Laura Quick; Richard D. Williams; Karen A. Hudson-Edwards; Cecilia Tortajada; Patrick Byrne; Tom J. Coulthard; Jenielyn T. Padrones; Rich Crane; Cris Reven L. Gibaga; Grigorios Vasilopoulos; et al. (Journal of Cleaner Production, 2024)

Phylogenomic analyses of multidrug resistant Corynebacterium striatum strains isolated from patients in a tertiary care hospital in the UK - Vartul Sangal; Emma C. L. Marrs; Andrew Nelson; John D. Perry (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Corynebacterium striatum is an emerging nosocomial pathogen. This is the first report showing the presence of three distinct multidrug resistant lineages of C. striatum among patients in a UK hospital. The presence of ErmX, Tet(W), Bla and AmpC proteins, and mutations in gyrA gene are associated with the resistance to clindamycin, doxycycline, penicillin and moxifloxacin, respectively. These strains are equipped with several corynebacterial virulence genes including two SpaDEF-type and a novel pilus gene cluster, which needs further molecular characterisation. This study highlights a need of developing an active surveillance strategy for routine monitoring and preventing potential cross-transmission among susceptible patients.

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

Nitrogen isotope (δ 15 N) patterns for amino acids in lemur bones are inconsistent with aridity driving megafaunal extinction in south‐western Madagascar - Sean W. Hixon; Emma A. Elliott Smith; Brooke E. Crowley; George H. Perry; Jeannot Randrianasy; Jean Freddy Ranaivoarisoa; Douglas J. Kennett; Seth D. Newsome (Journal of Quaternary Science, 2018)
Most endemic species with body masses >10 kg on Madagascar went extinct within the past 1000 years. The extent to which human predation, anthropogenic landscape transformation and aridification may separately or together explain this extinction pattern remains controversial. We present nitrogen isotope (δ 15 N) values of individual amino acids preserved in bones from now‐extinct Pachylemur insignis and extant Propithecus verreauxi from two subfossil sites in south‐western Madagascar: Tsirave and Taolambiby. The amino acid‐specific approach allows us to identify environmental signals that are otherwise difficult to recognize in bulk collagen δ 15 N values. Specifically, we use the δ 15 N values of source amino acids (phenylalanine and lysine) as a proxy for habitat aridity between ca . 4000 years ago and present and the spacing of δ 15 N values between trophic and source amino acids to quantify trophic levels for these two lemur species. Despite paleoenvironmental evidence for lowering water tables and the expansion of relatively arid savanna between 4000 and 1000 years ago, our isotope data suggest that these lemurs did not live in increasingly arid habitats and did not change their trophic level. Together, our results support the hypothesis that aridity alone did not play a major role in late Holocene megafaunal extinctions in south‐western Madagascar.

Follicular determinants of pregnancy establishment and maintenance - Ky G. Pohler; Thomas W. Geary; Jacqueline A. Atkins; George A. Perry; Emma M. Jinks; Michael F. Smith (Cell and Tissue Research, 2012)

Molecular distinction between true centric fission and pericentric duplication-fission - Jo Perry; Sara Nouri; Phung La; Art Daniel; Zhanhe Wu; Stuart Purvis-Smith; Emma Northrop; K. H. Andy Choo; Howard R. Slater (Human Genetics, 2005)